An efficient MILP framework for integrating nonlinear process dynamics and control in optimal production scheduling calculations. (2nd February 2018) - Kelley, Morgan T.; Pattison, Richard C.; Baldick, Ross; Baldea, Michael
Highlights: Focus on integrating dynamics and control in scheduling calculations. Closed-loop dynamics represented via surrogate modes in Hammerstein–Wiener or finite step response form identified from operating data. (Exact) linearization of surrogate models results in MILP integrated scheduling problem. Lagrangian relaxation exploits problem structure with excellent performance. Abstract: The emphasis currently placed on enterprise-wide decision making and optimization has led to an increased need for methods of integrating nonlinear process dynamics and control information in scheduling calculations. The inevitable high dimensionality and nonlinearity of first-principles dynamic process models makes incorporating them in scheduling calculations challenging. In this work, we describe a general framework for deriving data-driven surrogate models of the closed-loop process dynamics. Focusing on Hammerstein–Wiener and finite step response (FSR) model forms, we show that these models can be (exactly) linearized and embedded in production scheduling calculations. The resulting scheduling problems are mixed-integer linear programs with a special structure, which we exploit in a novel and efficient solution strategy. A polymerization reactor case study is utilized to demonstrate the merits of this method. Our framework compares favorably to existing approaches that embed dynamics in scheduling calculations, showing considerable reductions in computational effort.